Phosphoaluminosilicate glass and preparation method thereof, tempered glass and preparation method thereof, and glass product
By introducing specific ratios of phosphoaluminosilicate components into the glass, the problem of prone to cracking in existing high-alumina glass during transportation and processing is solved, and the glass is balanced with low melting point and high mechanical properties is improved. Resistance to fall shock and mechanical strength.
Patent Information
- Application Number
- CN202411519394.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-14
AI Technical Summary
Existing electronic grade high alumina glass is prone to rupture during transportation and processing, and in order to reduce production costs, glass is required to have a lower melting point, which leads to insufficient mechanical strength and fall resistance to impact of the glass.
A phosphaluminosilicate glass is provided, which includes a specific ratio of SiO2, Al2O3, P2O5, Na2O, K2O, MgO, Sc2O3, ZnO and ZrO2 components, and through the synergistic action of these components, the melting temperature of the glass is reduced, At the same time, it improves its mechanical properties.
It achieves the balance of low melting point and high mechanical properties of glass, improves the resistance to drop impact and mechanical strength of glass, and is suitable for the processing of electronic-grade display panels.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of glass products, and in particular to a phosphoaluminosilicate glass and a preparation method thereof, tempered glass and a preparation method thereof, and glass products. Background Art
[0002] The thickness of electronic grade high aluminum glass is generally less than 0.7mm. It needs to go through multiple processing steps from the production base to the display panel processing plant. These processes put forward stringent requirements on the mechanical strength and drop impact resistance of the glass. When the glass is subjected to external force, the impact force is distributed over a very small area, which is easy to cause stress concentration, exceeding the strength limit of the glass, and causing the glass to break.
[0003] At the same time, in order to facilitate production, reduce production line investment and production process costs, reduce the erosion of kiln refractory materials and the service life of supporting equipment caused by high melting temperatures and volatile raw materials, glass is required to have a lower melting point. Summary of the invention
[0004] Based on this, it is necessary to provide a phosphoaluminosilicate glass with a low melting temperature and high mechanical properties and a preparation method thereof. In addition, a tempered glass with good impact resistance and a preparation method and glass products thereof are also provided.
[0005] In a first aspect of the present application, a phosphoaluminosilicate glass is provided, which comprises the following components by weight percentage:
[0006] SiO 2 58.5%~68.5%,
[0007] Al 2 O 3 10%~15%,
[0008] P 2 O 5 0.5%~3%,
[0009] Na 2 O 13%~17.5%,
[0010] K 2 O 1.4%~4.5%,
[0011] MgO 1%~4.5%,
[0012] Sc 2 O 3 0.02%~0.3%,
[0013] ZnO 0.1%~2% and
[0014] ZrO 20.4%~1.3%;
[0015] Among them, Sc 2 O 3 , ZnO and ZrO 2 The mass percentage content satisfies the following relationship (I): 0.03≤W Sc2O3 / (W ZrO2 +W ZnO )≤0.21; P 2 O 5 With Al 2 O 3 The mass percentage content satisfies the following relationship (II): 0.05≤W P2O5 / (W Al2O3 +W P2O5 )≤0.23; where W Sc2O3 , W ZrO2 , W ZnO , W P2O5 , W Al2O3 and W P2O5 Respectively represent the mass percentage of each component in the phosphoaluminosilicate glass.
[0016] The above-mentioned aluminophosphorus silicate glass includes SiO 2 、Al 2 O 3 , P 2 O 5 、Na 2 O.K 2 O, MgO, Sc 2 O 3 , ZnO and ZrO 2 Through the synergistic effect of the distribution ratio of each component, a phosphoaluminosilicate glass with low melting temperature and high mechanical properties such as Vickers hardness and Young's modulus is obtained; wherein P 2 O 5 and Sc 2 O 3 The introduction of P 2 O 5 and Al 2 O 3 The content relationship can reduce the melting temperature of glass and control Sc 2 O 3 、ZrO 2 and ZnO can further improve the mechanical properties of phosphoaluminosilicate glass.
[0017] In some embodiments, the thermal expansion coefficient of the phosphoaluminosilicate glass at 50°C to 350°C is 80×10 -7 / ℃~98×10 -7 / ℃; and / or,
[0018] The softening point of the phosphoaluminosilicate glass is 715°C to 755°C.
[0019] In some embodiments, the Young's modulus of the phosphoaluminosilicate glass is 72 GPa to 81 GPa; and / or,
[0020] The Vickers hardness of the phosphoaluminosilicate glass is 570 MPa to 630 MPa.
[0021] In a second aspect, the present application provides a method for preparing the phosphoaluminosilicate glass of the first aspect, comprising the following steps:
[0022] Weighing raw materials according to the composition of the phosphoaluminosilicate glass;
[0023] The raw materials are sequentially mixed, melted, formed and annealed.
[0024] In some embodiments, the melting temperature is 1540° C. to 1600° C.; and / or,
[0025] The temperature of the annealing treatment is 550° C. to 600° C., and the time of the annealing treatment is 12 h to 24 h.
[0026] In some embodiments, before the forming step, the step of clarification and homogenization of the molten glass is also included.
[0027] In a third aspect of the present application, there is provided a strengthened glass obtained by chemically tempering the phosphoaluminosilicate glass described in the first aspect.
[0028] In some embodiments, the surface compressive stress of the tempered glass is 780 MPa to 1025 MPa; and / or,
[0029] The depth of the surface compressive stress layer of the tempered glass is 25 μm to 38 μm; and / or,
[0030] The Vickers hardness of the tempered glass is 680 MPa to 840 MPa.
[0031] In a fourth aspect, the present application provides a method for preparing the tempered glass described in the third aspect, comprising the following steps:
[0032] The aluminophosphorus silicate glass is chemically tempered in molten salt.
[0033] In a fifth aspect of the present application, a glass product is provided, comprising the tempered glass described in the third aspect. DETAILED DESCRIPTION
[0034] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively below, and preferred embodiments of the present invention are given. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. It should be understood that the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0035] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0036] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0037] In one embodiment of the present application, a phosphoaluminosilicate glass is provided, which comprises the following components by weight percentage:
[0038] SiO 2 58.5%~68.5%,
[0039] Al 2 O 3 10%~15%,
[0040] P 2 O 5 0.5%~3%,
[0041] Na 2 O 13%~17.5%,
[0042] K 2 O 1.4%~4.5%,
[0043] MgO 1%~4.5%,
[0044] Sc 2 O 3 0.02%~0.3%,
[0045] ZnO 0.1%~2% and
[0046] ZrO 2 0.4%~1.3%;
[0047] Among them, Sc 2 O 3 , ZnO and ZrO 2 The mass percentage content satisfies the following relationship (I): 0.03≤W Sc2O3 / (W ZrO2 +W ZnO )≤0.21; P 2 O 5 With Al 2 O 3 The mass percentage content satisfies the following relationship (II): 0.05≤W P2O5 / (W Al2O3 +W P2O5 )≤0.23; where W Sc2O3 , W ZrO2 , W ZnO , W P2O5 , W Al2O3 and W P2O5 They respectively represent the mass percentage of each component in the phosphoaluminosilicate glass.
[0048] The above-mentioned aluminophosphorus silicate glass includes SiO 2 、Al 2 O 3 , P 2 O 5 、Na 2 O.K 2 O, MgO, Sc 2 O 3 , ZnO and ZrO 2 The components are used to obtain a phosphoaluminosilicate glass with low melting temperature, high Vickers hardness and Young's modulus and other high mechanical properties through the synergistic effect of the distribution ratio of each component; wherein P 2 O 5 and Sc 2 O 3 The introduction of P 2 O 5 and Al 2 O 3 The content relationship can reduce the melting temperature of glass and control Sc 2 O 3 、ZrO 2 and ZnO can further improve the mechanical properties of phosphoaluminosilicate glass.
[0049] SiO 2 It is the component that forms the glass network skeleton and is also the largest component in phosphoaluminosilicate glass. 2 The content of glass [SiO 4]The network integrity decreases, which increases the linear expansion coefficient of the glass and reduces its stability. 2 Increasing the content can improve the mechanical strength, chemical stability and thermal stability of the glass; however, if SiO 2 If the content of SiO exceeds 68.5%, the high temperature viscosity of the glass increases, which is not conducive to the industrial production of the composition. 2 The mass percentage of SiO in phosphoaluminosilicate glass is in the range of 58.5% to 68.5%. 2 The mass percentage of SiO can be 58.5%, 59.0%, 59.5%, 60.0%, 60.5%, 61.0%, 61.5%, 62.0%, 62.5%, 63.0%, 64.5%, 65.0%, 65.5%, 66.0%, 66.5%, 67.0%, 67.5%, 68.0% or 68.5%. Further, SiO in the phosphoaluminosilicate glass 2 The mass percentage content can be a range value consisting of any two of the above-mentioned point values as end values.
[0050] Al 2 O 3 It makes the glass network structure more complete and improves the chemical stability, elastic modulus and hardness of the glass. 3+ Formation of glass formers [AlO 4 ], forming larger void channels in the glass network structure, which is beneficial to the exchange of alkali metal ions to obtain the maximum surface compressive stress (CS) and depth of compressive stress layer (DOL). 2 O 3 The preferred mass percentage of Al is above 10%. 2 O 3 The content of Al in the phosphate aluminosilicate glass provided by the present application is not more than 15%; this can reduce the viscosity of the glass liquid, facilitate glass production, and obtain high-aluminum glass with a lower softening point. 2 O 3 The mass percentage of Al in phosphoaluminosilicate glass is 10%~15%. 2 O 3 The mass percentage of Al in the phosphoaluminosilicate glass may be 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5% or 15%. 2 O 3 The mass percentage content can be a range value consisting of any two of the above-mentioned point values as end values.
[0051] P2 O 5 On the one hand, it can reduce the high temperature viscosity of the glass to promote melting and clarification. 4 ] unit is fixed in the glass structure, thus improving the network structure of the glass. On the other hand, P 2 O 5 The introduction of phosphorus will reduce the chemical stability of the glass, and when the content is too high, the glass is prone to crystallization; from the cost point of view, the price of phosphorus-containing raw materials is relatively high, and the production of high-phosphorus glass is also difficult. 2 O 5 The mass percentage of P in phosphoaluminosilicate glass is 0.5%~3%. 2 O 5 The mass percentage of can be 0.5%, 0.8%, 1%, 1.2%, 1.4%, 1.5%, 1.6%, 1.8%, 2%, 2.2%, 2.5%, 2.8% or 3%. 2 O 5 The mass percentage content can be a range value consisting of any two of the above-mentioned point values as end values.
[0052] Since the bond energy of Si-O and Al-O is large, the required melting temperature is high, and the formed [SiO 4 ] and [AlO 4 ] The unit structure has high rigidity and is not easy to absorb external impact. Therefore, this application uses P 2 O 5 , and control P 2 O 5 and Al 2 O 3 The mass percentage of satisfies the following relationship: 0.05≤W P2O5 / (W Al2O3 +W P2O5 )≤0.23, using PO bonds to replace some Si-O bonds and Al-O bonds, improving the glass network skeleton structure, forming [PO 4 ] layered or chain-like structural units, so that the glass is more likely to slip or plastically deform when subjected to external forces, thereby improving the glass's resistance to drop impact. As an example, W P2O5 / (W Al2O3 +W P2O5 ) may have a value of 0.05, 0.08, 0.10, 0.12, 0.14, 0.15, 0.16, 0.18, 0.20, 0.22, or 0.23. P2O5 / (W Al2O3 +W P2O5 ) can be a range value consisting of any two of the above point values as end values.
[0053] Sc 2 O 3 Can reduce the high temperature viscosity of glass, Sc 3+ The electric price is high, the radius is large, and it mainly plays an accumulation role under low temperature conditions, improving the density of the glass network, improving the strength of the glass network structure and Young's modulus, and increasing the surface compressive stress after ion exchange. 2 O 3 The price is high, and excessive introduction may increase production costs; in addition, Sc 2 O 3 Too much introduction may reduce the metal ion diffusion coefficient, thereby reducing the chemical strengthening effect. 2 O 3 The mass percentage of Sc in phosphoaluminosilicate glass is 0.02%~0.3%. 2 O 3 The mass percentage of Sc can be 0.02%, 0.04%, 0.05%, 0.06%, 0.08%, 0.10%, 0.12%, 0.14%, 0.15%, 0.16%, 0.18%, 0.20%, 0.22%, 0.24%, 0.25%, 0.26%, 0.28% or 0.3%. 2 O 3 The mass percentage content can be a range value consisting of any two of the above-mentioned point values as end values.
[0054] Na 2 O is the outer body of the glass network, which can promote the melting of glass batch materials and is also the main component of chemical strengthening. 2 When the content of O exceeds 17.5%, the linear expansion coefficient of the glass increases, the stability deteriorates, and it is easy to crack, which is not conducive to industrial production and post-processing. If it is less than 13%, the increase in the linear expansion coefficient cannot be effectively controlled, and it is not conducive to chemical strengthening and reducing the surface ion exchange compressive stress of the glass surface. Therefore, the Na in the phosphoaluminosilicate glass provided by the application 2 The mass percentage of O is 13% to 17.5%. As an example, Na in phosphoaluminosilicate glass 2 The mass percentage of O can be 13%, 13.2%, 13.4%, 13.5%, 13.6%, 13.8%, 14.0%, 14.2%, 14.5%, 14.6%, 14.8%, 15.0%, 15.2%, 15.4%, 15.5%, 15.6%, 15.8%, 16.0%, 16.5%, 16.8%, 17.0%, 17.2% or 17.5%. Further, the mass percentage of Na in the phosphoaluminosilicate glass can be 13%, 13.2%, 13.4%, 13.5%, 13.6%, 13.8%, 14.0%, 14.2%, 14.5%, 14.6%, 14.8%, 15.0%, 15.2%, 15.4%, 15.5%, 15.6%, 15.8%, 16.0%, 16.5%, 16.8%, 17.0%, 17.2% or 17.5%. 2The mass percentage of O can be a range value consisting of any two of the above-mentioned point values as end values.
[0055] K 2 O is with Na 2 O components of the same nature, adding K 2 O and Na 2 O promotes high-temperature melting and clarification of glass, improves chemical strengthening effect, and inhibits a significant increase in the coefficient of linear expansion (CTE) through the mixed alkali effect. 2 If the content of O is too high, the ion exchange capacity of the glass will decrease and the linear expansion coefficient will increase. 2 The preferred range of O mass percentage is 1.4%-4.5%. As an example, K in phosphoaluminosilicate glass 2 The mass percentage of O can be 1.4%, 1.5%, 1.8%, 2.0%, 2.2%, 2.5%, 2.8%, 3.0%, 3.2%, 3.4%, 3.5%, 3.6%, 3.8%, 4.0%, 4.2%, 4.4% or 4.5%. 2 The mass percentage of O can be a range value consisting of any two of the above-mentioned point values as end values.
[0056] MgO helps to lower the melting temperature of glass, reduce the tendency of glass crystallization, and at the same time can increase the elastic modulus of glass and inhibit the occurrence of cracks. However, if the mass content of MgO is higher than 4.5%, the linear expansion coefficient of the glass increases. If the mass content of MgO is lower than 1%, the viscosity of the glass melt will increase and the solubility will decrease. Therefore, the preferred range of the mass percentage of MgO in the phosphoaluminosilicate glass provided in the present application is 1% to 4.5%. As an example, the mass percentage of MgO in the phosphoaluminosilicate glass can be 1%, 1.2%, 1.3%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.6%, 3.7%, 3.8%, 4%, 4.2%, 4.4% or 4.5%. Further, the mass percentage of MgO in the phosphoaluminosilicate glass can be a range value composed of any two of the above point values as end values.
[0057] ZnO can increase the mechanical properties of glass such as Young's modulus and hardness, and the increase in the linear expansion coefficient of glass is not obvious. However, too much ZnO can greatly reduce the thermal properties of glass. Therefore, the mass percentage of ZnO in the phosphoaluminosilicate glass provided in the present application is 0.1% to 2%. As an example, the mass percentage of ZnO in the phosphoaluminosilicate glass can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2.0%. Further, the mass percentage of ZnO in the phosphoaluminosilicate glass can be a range value composed of any two of the above point values as end values.
[0058] ZrO 2 It is a component that can increase the ion exchange power during the glass ion exchange process, and at the same time can improve the hardness and Young's modulus of the glass, and improve the weather resistance and stability of the glass; but too much ZrO 2 The melting temperature of the glass will rise significantly. 2 The mass percentage of ZrO is 0.4%~1.3%. As an example, ZrO in phosphoaluminosilicate glass 2 The mass percentage of ZrO can be 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2% or 1.3%. 2 The mass percentage content can be a range value consisting of any two of the above-mentioned point values as end values.
[0059] As an example, W Sc2O3 / (W ZrO2 +W ZnO ) can have a value of 0.003, 0.004, 0.005, 0.006, 0.007, 0.012, 0.014, 0.015, 0.018, 0.020, and 0.021. Further, W Sc2O3 / (W ZrO2 +W ZnO ) can be a range value consisting of any two of the above point values as end values.
[0060] In some embodiments, the density of the phosphoaluminosilicate glass is 2.40 g / cm 3 ~2.6g / cm 3 Furthermore, the density of phosphoaluminosilicate glass is 2.47 g / cm 3 ~2.51g / cm 3 Glass with a density within the above range has an excellent characteristic of being lightweight.
[0061] In some embodiments, the thermal expansion coefficient of the phosphoaluminosilicate glass at 50°C to 350°C is 80×10 -7 / ℃~98×10 -7 / ℃.
[0062] In some embodiments, the softening point of the phosphoaluminosilicate glass is 715° C. to 755° C. The softening point of the phosphoaluminosilicate glass is within this relatively low temperature range, which is more conducive to hot bending and deep processing of products with high requirements on appearance and feel, such as 2.5D, 3D and 3.5D curved glass, thereby helping to expand the use of glass.
[0063] In some embodiments, the strain point temperature of the phosphoaluminosilicate glass is 520° C. to 600° C. Further, the strain point temperature of the phosphoaluminosilicate glass is 530° C. to 590° C. Glass with a strain point in this range can be subjected to thermal processing conditions of 200° C. to 400° C. without significant deformation.
[0064] In some embodiments, the Young's modulus of the phosphoaluminosilicate glass is 72 GPa to 81 GPa. Further, the Young's modulus of the phosphoaluminosilicate glass is 74 GPa to 81 GPa.
[0065] In some embodiments, the Vickers hardness of the phosphoaluminosilicate glass is 570 MPa to 630 MPa. Further, the Vickers hardness of the phosphoaluminosilicate glass is 578 MPa to 627 MPa.
[0066] In some embodiments, the melting temperature T of the phosphoaluminosilicate glass is 2 The melting temperature of phosphoaluminosilicate glass is within this range, which can reduce the difficulty of industrial processing and also reduce the processing cost.
[0067] In one embodiment of the present application, a method for preparing phosphoaluminosilicate glass is provided, comprising the following steps:
[0068] Weigh the raw materials according to the composition of phosphoaluminosilicate glass;
[0069] The raw materials are mixed, melted, formed and annealed in sequence.
[0070] In some embodiments, melting refers to the step of melting raw materials into glass liquid under high temperature conditions. The melting temperature is 1540°C to 1600°C. As an example, the melting temperature can be 1540°C, 1550°C, 1560°C, 1570°C, 1580°C, 1590°C or 1600°C.
[0071] In some embodiments, before the forming step, the step of clarification and homogenization of the melted glass is also included. The clarification and homogenization is carried out in a conventional clarification and homogenization manner in the art.
[0072] In some embodiments, the temperature of the annealing treatment is 550° C. to 600° C. As an example, the temperature of the annealing treatment may be 550° C., 560° C., 570° C., 580° C., 590° C. or 600° C. Further, the temperature of the annealing treatment may be a range value consisting of any two of the above point values as end values.
[0073] In some embodiments, the annealing time is 12 hours to 24 hours. As an example, the annealing time can be 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours or 24 hours. Further, the annealing time can be a range value consisting of any two of the above point values as end values.
[0074] In one embodiment of the present application, there is provided a strengthened glass obtained by chemically tempering phosphoaluminosilicate glass.
[0075] In some embodiments, the surface compressive stress (CS) of the strengthened glass is 780 MPa to 1025 MPa. As an example, the surface compressive stress (CS) of the strengthened glass can be 780 MPa, 785 MPa, 790 MPa, 795 MPa, 800 MPa, 805 MPa, 810 MPa, 820 MPa, 850 MPa, 870 MPa, 900 MPa, 950 MPa, 960 MPa, 980 MPa, 1000 MPa, 1010 MPa, 1020 MPa or 1025 MPa. Further, the surface compressive stress (CS) of the strengthened glass can be a range value consisting of any two of the above point values as end values.
[0076] In some embodiments, the depth of the surface compressive stress layer (DOL) of the strengthened glass is 25 μm to 38 μm. As an example, the depth of the surface compressive stress layer (DOL) of the strengthened glass can be 25 μm, 26 μm, 27 μm, 28 μm, 29 μm, 30 μm, 31 μm, 32 μm, 33 μm, 34 μm, 35 μm, 36 μm, 37 μm or 38 μm.
[0077] In some embodiments, the Vickers hardness of the tempered glass is 680 MPa-890 MPa.
[0078] In some embodiments, the height of the ball drop of the tempered glass is 50 cm to 80 cm.
[0079] In one embodiment of the present application, a method for preparing tempered glass is provided, comprising the following steps:
[0080] The phosphoaluminosilicate glass is chemically toughened in molten salt.
[0081] In some embodiments, the molten salt is pure KNO 3 Salt.
[0082] In some embodiments, the temperature of the chemical tempering treatment is 395° C. to 430° C. As an example, the temperature of the chemical tempering treatment may be 395° C., 400° C., 410° C., 420° C., or 430° C. Further, the temperature of the chemical tempering treatment may be a range value consisting of any two of the above point values as end values.
[0083] In some embodiments, the time of chemical tempering treatment is 1.5h~4h. As an example, the time of chemical tempering treatment can be 1.5h, 2h, 2.5h, 3h, 3.5h or 4h. Further, the time of chemical tempering treatment can be a range value consisting of any two of the above point values as end values.
[0084] In one embodiment of the present application, a glass product is provided, comprising the above-mentioned tempered glass.
[0085] In some embodiments, the glass product can be at least one of an electronic device display, a solar photovoltaic module, automotive glass, and architectural glass. For example, the tempered glass can be used as the outer screen glass of an electronic device display.
[0086] In order to make the purpose, technical solutions and advantages of the present invention more concise and clear, the present invention is described with the following specific embodiments, but the present invention is by no means limited to these embodiments. The embodiments described below are only preferred embodiments of the present invention, which can be used to describe the present invention and cannot be understood as limiting the scope of the present invention. It should be pointed out that any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
[0087] The following are specific embodiments.
[0088] The preparation process and testing method of the phosphoaluminosilicate glass and the tempered glass of Examples 1 to 20 and Comparative Examples 1 to 4 are as follows:
[0089] (1) Prepare the ingredients according to the designed component ratios in Tables 1 to 4; then perform mechanical mixing for 0.5 h to 1 h.
[0090] (2) Pour the mixed ingredients into a platinum-rhodium crucible and melt them at 1540°C~1600°C; then clarify and homogenize them for 6h~10h to obtain glass liquid.
[0091] (3) The glass liquid is poured into a stainless steel mold for forming, annealed at 550°C to 600°C for 12 h to 24 h, and then cooled to room temperature to obtain phosphoaluminosilicate glass.
[0092] (4) The phosphoaluminosilicate glass products are sliced into 300*300*1mm slices using a wire cutting machine, and then subjected to coarse grinding → ordinary cleaning → fine grinding → ultrasonic cleaning → CNC grinding and chamfering → polishing and finishing.
[0093] (5) Place the processed glass piece in molten pure KNO at 395℃~430℃ 3 Chemical tempering in salt was carried out for 1.5h~4h, and finally the physical and chemical properties of the glass samples were tested.
[0094] The test method is as follows:
[0095] The density of glass is determined by the Archimedean method.
[0096] Young's modulus was measured using a bending resonance method.
[0097] The expansion coefficient (50°C~350°C) was measured using a German NETZSCH DIL-402PC horizontal expansion instrument with a heating rate of 5°C / min.
[0098] The compressive stress (CS) and depth of compressive stress layer (DOL) of the glass surface after chemical tempering were measured using a FSM-6000LE surface stress meter.
[0099] The Vickers hardness is measured using a Vickers hardness tester in accordance with ASTM E-384.
[0100] The glass strain point, annealing point and softening point are determined according to ASTM C-336 and ASTM C-338.
[0101] The melting temperature is measured by a high temperature viscometer and then calculated by the Vogel-Fulcher-Tamann formula. 2 .
[0102] Drop ball height test: Place the tempered glass sheet on a hollow acrylic plate bracket, and use a drop ball test device to drop a 64g solid steel ball at the center of the glass at a predetermined height. The drop ball height starts at 45cm and increases by 5cm each time until the glass breaks, and the corresponding height is recorded.
[0103] The physical and chemical property test data of the phosphoaluminosilicate glass and the tempered glass prepared in each embodiment and comparative example are shown in Table 1 to Table 4.
[0104] Table 1
[0105]
[0106] Table 2
[0107]
[0108] Table 3
[0109]
[0110] Table 4
[0111]
[0112] From the data in Tables 1 to 4, it can be seen that the SiO 2 、Al 2 O 3 , P 2 O 5 、Na 2 O.K 2 O, MgO, Sc 2 O 3 , ZnO and ZrO 2 The composition of the aluminum phosphate silicate glass has a density of 2.474g / cm 3 ~2.515g / cm 3 , the linear expansion coefficient (50℃~350℃) is 81.3×10 -7 / ℃~97.8×10 -7 / ℃, Young's modulus is 74.1GPa~80.4GPa, melting temperature T 2 The Vickers hardness of chemically tempered glass reaches 685MPa~832MPa, the surface compressive stress (CS) of chemically tempered tempered glass reaches 785MPa~1021MPa, the depth of compressive stress layer (DOL) reaches 25.6μm~36.6μm, and the ball drop height reaches 55cm~80cm.
[0113] Comparing Example 3 with Comparative Example 1, the composition of the phosphoaluminosilicate glass in Example 3 and Comparative Example 1 is similar, but the Sc 2 O 3 The component content is 0.4%, which is higher than the range of this application, and the intensity factor W Sc2O3 / (W ZrO2 +W ZnO ) is as high as 0.25. The results show that after tempering, the CS value (764MPa), DOL (24.4μm) and ball drop height (45cm) of Comparative Example 1 are lower than those of Example 3 (837MPa), DOL (32.3μm) and ball drop height (70cm). This may be because the Sc2 O 3 When the content is high, too much free Sc 3+ It hinders the exchange of sodium and potassium ions, resulting in a decrease in the CS and DOL values of the tempered glass, while also reducing the impact resistance of the tempered glass.
[0114] Comparing Example 10 with Comparative Example 2, the composition of the phosphoaluminosilicate glass in Example 10 and Comparative Example 2 is similar, but the Sc 2 O 3 The component content is 0.01%, which is lower than the scope of this application, and the intensity factor W Sc2O3 / (W ZrO2 +W ZnO ) is only 0.01. The results show that the Young's modulus of the phosphate aluminosilicate glass of Comparative Example 2 is 72.2 GPa, and the Young's modulus of the phosphate aluminosilicate glass of Example 10 is 74.1 GPa; after the treatment, the Vickers hardness of the tempered glass of Comparative Example 2 is 696 MPa, while the Vickers hardness of the tempered glass of Example 10 is 827 MPa; the CS value (784.5 MPa), DOL (22.4 μm) and the ball drop height (40 cm) of the tempered glass of Comparative Example 2 are all lower than the CS value (954 MPa), DOL (33.4 μm) and the ball drop height (65 cm) of Example 10. This may be because the free Sc in Comparative Example 2 3+ If it is too little, it cannot effectively make the glass network structure denser, resulting in a decrease in the Vickers hardness and Young's modulus of the glass, while also reducing the impact resistance of the tempered glass.
[0115] Comparing Example 6 with Comparative Example 3, the composition of the phosphoaluminosilicate glass in Example 6 and Comparative Example 3 is similar, but the composition of the phosphoaluminosilicate glass in Comparative Example 3 is similar. 2 O 5 The component content is 3.6%, which is higher than the scope of this application, and W P2O5 / (W Al2O3 +W P2O5 ) value reaches 0.24. The results show that the thermal expansion coefficient of the phosphoaluminosilicate glass of comparative example 3 is as high as 102.5×10-7 / ℃, while the thermal expansion coefficient of the phosphoaluminosilicate glass of embodiment 6 is only 90.3×10-7 / ℃. Moreover, after comparison, it can be seen that the mechanical properties of the glass product of embodiment 6 before and after tempering are better than those of the glass product of comparative example 3 before and after tempering. This may be because P 2 O 5 When the content is too high, the glass expansion coefficient will increase, causing the glass network structure to loosen, thereby reducing the mechanical properties of the glass before and after tempering.
[0116] Comparing Example 17 with Comparative Example 4, the composition of the phosphoaluminosilicate glass in Example 17 and Comparative Example 4 is similar, but the composition of the phosphoaluminosilicate glass in Comparative Example 4 is similar. 2 O 5 The component content is 0.3%, which is lower than the scope of this application, and W P2O5 / (W Al2O3 +W P2O5 ) is only 0.02. The melting temperature of the phosphoaluminosilicate glass of Example 17 is 1584°C, while the melting temperature of the phosphoaluminosilicate glass of Comparative Example 4 is as high as 1619°C. This may be because the P 2 O 5 The low content causes the melting temperature of phosphoaluminosilicate glass to increase significantly, which in turn greatly increases the difficulty and cost of industrial production.
[0117] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0118] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims, and the description can be used to interpret the content of the claims.
Claims
1. A phosphoaluminosilicate glass, characterized in that: Calculated by mass percentage, it includes the following components: SiO2 58.5%~68.5%, Al2O3 10%~15%, P2O5 0.5%~3%, Na2O 13%~17.5%, K2O 1.4%~4.5%, MgO 1%~4.5%, Sc2O3 0.02%~0.3%, ZnO 0.1%~2% and ZrO2 0.4%~1.3%; Among them, the mass percentage of Sc2O3, ZnO and ZrO2 satisfies the following relationship: 0.03≤W Sc2O3 / (W ZrO2 +W ZnO )≤0.21; the mass percentage of P2O5 and Al2O3 satisfies the following relationship: 0.05≤W P2O5 / (W Al2O3 +W P2O5 )≤0.23; where W Sc2O3 , W ZrO2 , W ZnO , W P2O5 , W Al2O3 and W P2O5 Respectively represent the mass percentage of each component in the phosphoaluminosilicate glass.
2. The phosphoaluminosilicate glass according to claim 1, characterized in that The thermal expansion coefficient of the phosphoaluminosilicate glass at 50°C to 350°C is 80×10 -7 / ℃~98×10 -7 / ℃; and / or, The softening point of the phosphoaluminosilicate glass is 715°C to 755°C.
3. The phosphoaluminosilicate glass according to claim 1, wherein: The Young's modulus of the phosphoaluminosilicate glass is 72 GPa to 81 GPa; and / or, The Vickers hardness of the phosphoaluminosilicate glass is 570 MPa to 630 MPa.
4. The method for preparing phosphoaluminosilicate glass according to any one of claims 1 to 3, characterized in that: The steps include: Weighing raw materials according to the composition of the phosphoaluminosilicate glass; The raw materials are sequentially mixed, melted, formed and annealed.
5. The preparation method according to claim 4, characterized in that: The melting temperature is 1540°C to 1600°C; and / or, The temperature of the annealing treatment is 550° C. to 600° C., and the time of the annealing treatment is 12 h to 24 h.
6. The preparation method according to any one of claims 4 to 5, characterized in that: Before the forming step, the method further includes the steps of clarification and homogenization of the melted glass.
7. A tempered glass, characterized in that: The glass is obtained by chemically tempering the phosphoaluminosilicate glass as described in any one of claims 1 to 3.
8. The tempered glass according to claim 7, wherein: The surface compressive stress of the tempered glass is 780MPa-1025MPa; and / or, The depth of the surface compressive stress layer of the tempered glass is 25 μm to 38 μm; and / or, The Vickers hardness of the tempered glass is 680 MPa to 840 MPa.
9. The method for preparing tempered glass according to any one of claims 7 to 8, characterized in that: The steps include: The aluminophosphorus silicate glass is chemically tempered in molten salt.
10. A glass product, characterized in that: The tempered glass comprises the tempered glass according to any one of claims 7 to 8.
Citation Information
Patent Citations
Alumina silicate glass and preparation method thereof as well as cover plate and display device
CN109437555A
Aluminosilicate glass, preparation method thereof, reinforced glass and application thereof
CN110510874A
Aluminosilicate glass, tempered glass, preparation method of the tempered glass, and display device
CN110615611A
Aluminum silicate glass, toughened glass, preparation method of toughened glass, cover plate, back plate and device
CN110642514A
Aluminosilicate glass, preparation method and application thereof
CN111825331A